Analisis Hadis-Hadis tentang Solat Wanita di Masjid - Muhammad Shulhi Alhadi Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Listening to idain sermons, arofat is mandatory for women even when menstruating. The last female Shof rule. The way to pray for the priest must be followed by both men and women. It is not permissible for men to be alone on the sof, except for women alone. Makmum in front is an example of the sof behind him. Do not precede the movement of the priest, whether male or female congregation. The Imam's appeal to the general public so that the lines are tight and straight. How to remind priests who forgot to understand women with subhanalloh sentences instead of clapping. Set the shof or line of men in front then boys, girls and women behind. Interlocking Prayers to the Mosque. Rosul's routine prayers go to the mosque. Recitation of women praying at dawn while on the road. The male congregation leaves after the woman is away so that rape does not occur. Rukhsoh Women pray to the mosque.